A multifuncionalidade do item agora através dos séculos: uma análise na fala e na escrita - Oliveira, Maria José de (2018)
This research aims to analyze the uses and process of grammaticalization of the item now under a panchronic approach correlated with the verification of aspects related to frequency of use, syntactic-semantic-discursive functions, order of placement and application of the principles and mechanisms of grammaticalization, considering the periods XIV until the first half of XVI; second half of XVI - XVII and XVIII - XX in data of writing and XX and XXI in data of speech and writing, aiming the verification of what is becoming regular in the language in relation to the functional behavior of the element. For this, the Portuguese-CDP Corpus (DAVIES; FERREIRA, 2006) is used; Corpus CE-DOHS. Electronic Corpus of Historical Documents of the Sertão (FAPESB 5566/2010); Banco conversacional de Natal (FURTADO DA CUNHA [org.], 2010), in addition to the chronicle of news & non-news chronicle (ANDRADE, 1974) is an analysis that is anchored in functionalist theory, specifically turning and the study of Givón (1979, 2001, 2005), Hopper and Traugott (2003), Heine and Kuteva (2007), Bybee (2006, 2010), among others. The work is divided into two focuses of approach: the first deals with the now through the centuries in an evolutionary description of uses in the panchronic perspective in specific genres of writing (letters and chronicles); the second focus deals with the item in the modalities of spoken and written language, through a comparison between uses according to the modalities of use, in the synchronic perspective of letter and chronic genres versus talk genre, of more recent periods. In relation to the values assumed by the item, through the times, the results indicate the tendency of the now occur in all the synchrony in a scalar path, adverb> conjunction> marker, in which the time value stands out as the most frequent function, however, it is possible to observe that the changes operate in a parallel way, because, as the item acts in the temporal function, it also acts with more textual / discursive values. Concerning the syntactic order, the AV order is considered to be the champion of the speaker / scribe preference, both from the synchronous and diachronic points of view, being exceeded, in the most recent periods, when the connector / connector function becomes more salient , favoring the order IO. In this way, it is possible that there is a logical-semantic correlation between semantic values and the established order. Thus, the data instigate to visualize an in-process grammaticalization when attesting the item in the exercise of values whose path can be represented by the cline of TIME> TEXT> SPEECH, verifying a gradual migration of the element in the direction of values (+ referential) values (-referential), both in writing through the ages, and in speech and writing of more recent centuries. This change is also driven by the syntactic order that gradually changes as the item changes its function.